A comparative genomic hybridization approach to study gene copy number variations among chinese hamster cell lines. Issue 8 (12th May 2017) - Vishwanathan, Nandita; Bandyopadhyay, Arpan; Fu, Hsu‐Yuan; Johnson, Kathryn C.; Springer, Nathan M.; Hu, Wei‐Shou
ABSTRACT: Chinese Hamster Ovary (CHO) cells are aneuploid in nature. The genome of recombinant protein producing CHO cell lines continuously undergoes changes in its structure and organization. We analyzed nine cell lines, including parental cell lines, using a comparative genomic hybridization (CGH) array focused on gene‐containing regions. The comparison of CGH with copy‐number estimates from sequencing data showed good correlation. Hierarchical clustering of the gene copy number variation data from CGH data revealed the lineage relationships between the cell lines. On analyzing the clones of a clonal population, some regions with altered genomic copy number status were identified indicating genomic changes during passaging. A CGH array is thus an effective tool in quantifying genomic alterations in industrial cell lines and can provide insights into the changes in the genomic structure during cell line derivation and long term culture. Biotechnol. Bioeng. 2017;114: 1903–1908. © 2017 Wiley Periodicals, Inc. Abstract : Chinese hamster ovary (CHO) cell lines are the major workhorses of the biopharmaceutical industry. Despite their omnipresence, very little is known about the genomic stability of these cell lines in their long lifetime from cell line development to end‐of‐production. By using CGH methodology, this paper provides insight into these genomic differences for several CHO cell lines and demonstrates the power of genomic tools in advancing scientific understanding of biopharmaceutical protein production.